Design of an Exploratory Experiment in Teaching for Engineering Education Accreditation: Fluoride Geochemical Simulation during Water–Rock Interactions under the Effect of Seawater Intrusion - Chen, Qiao; Wang, Xuewenyu; Yin, Huiyong; Feng, Jianguo (Sustainability, 2023)
Engineering education is critical for the creation of a more sustainable world, and engineering education accreditation has become the current trend for reform in higher education worldwide. Traditional replication experiment-based teaching cannot meet the standards of engineering education accreditation, and integrating the ideas of engineering education accreditation into experimental teaching is an important aspect of practical teaching. Taking fluoride evolution simulation during water–rock interactions under the effect of seawater intrusion as an example, an exploratory experiment was designed with the idea of engineering education accreditation. The experiment concluded that leached fluoride increases with increasing ratios of seawater and brine water, NaCl levels, and NaHCO3 levels, but with decreasing CaCl2 levels, which confirms that seawater intrusion deeply affects fluoride evolution. The saturation index and Fourier Transform Infrared analyses indicate that Ca2+ restriction and exchange of F with O–H and Si–O–Si are responsible for fluoride leaching. The experiment was characterized by deeper theory, logicality, and openness, and was also multi-schematic and exploratory. Therefore, it is an ideal subject matter to develop an exploratory experiment. A reasonable teaching link was designed to integrate the ideas of engineering education accreditation. Students were required to creatively and personally devise an experimental design and an expansion to the experiment based on the given databases and other relevant literature and to cooperate and discuss in groups. The experiment not only integrates basic knowledge of water–rock interactions, but also cultivates the awareness of and ability to analyze and solve problems, innovative thinking, scientific literacy, and teamwork. Meanwhile, the experiment effectively supports the graduate requirements of various subjects, including Design/Development Solutions, Research, Applying Modern Tools, Individual and Teams, and Communication.